Promoting equity : gender-neutral job evaluation for equal pay : a step-by-step guide - Chicha, Marie-Thérèse, 1943- (International Labour Office, 2008)
The publication is based on a comparative review of the job evaluation methods, guides and other materials that have been developed and used in different countries, as well as on case studies and research in gender studies and in human resources management.